2014
DOI: 10.1007/s00256-013-1800-7
|View full text |Cite
|
Sign up to set email alerts
|

Increasing lateral tibial slope: is there an association with articular cartilage changes in the knee?

Abstract: Our results show a statistically significant association between increasing LTS and worsening cartilage degenerative changes in the medial patella and the lateral tibial plateau. We speculate that increased LTS may result in increased femoral glide over the lateral tibial plateau with subsequent increased external rotation of the femur predisposing to patellofemoral articular changes. Future arthroscopic studies are needed to further confirm our findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
1
4
1
Order By: Relevance
“…Prior work has shown that increased posterior–inferior directed slope of the tibial plateau is associated with increased risk of suffering an ACL and ACL graft injury, and the increased lateral compartment posterior–inferior directed slopes found in the current study (3.6° for the ACL‐LM group and 1.6 for the ACL group) further exacerbates the chance of a second injury to the ACL graft . In addition, there is evidence that geometry of the articular cartilage and tibial plateau subchondral bone are associated with worsening cartilage degenerative changes in the lateral tibial plateau . Considered in combination, these findings introduce the hypothesis that once ACL injury has occurred, the same geometric characteristics associated with increased risk of suffering the index injury—increased posterior–inferior directed slope of the articular surfaces of the tibia—are also associated with increased risk of developing PTOA.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Prior work has shown that increased posterior–inferior directed slope of the tibial plateau is associated with increased risk of suffering an ACL and ACL graft injury, and the increased lateral compartment posterior–inferior directed slopes found in the current study (3.6° for the ACL‐LM group and 1.6 for the ACL group) further exacerbates the chance of a second injury to the ACL graft . In addition, there is evidence that geometry of the articular cartilage and tibial plateau subchondral bone are associated with worsening cartilage degenerative changes in the lateral tibial plateau . Considered in combination, these findings introduce the hypothesis that once ACL injury has occurred, the same geometric characteristics associated with increased risk of suffering the index injury—increased posterior–inferior directed slope of the articular surfaces of the tibia—are also associated with increased risk of developing PTOA.…”
Section: Discussionsupporting
confidence: 63%
“…[24][25][26] In addition, there is evidence that geometry of the articular cartilage and tibial plateau subchondral bone are associated with worsening cartilage degenerative changes in the lateral tibial plateau. 27 Considered in combination, these findings introduce the hypothesis that once ACL injury has occurred, the same geometric characteristics associated with increased risk of suffering the index injury-increased posterior-inferior directed slope of the articular surfaces of the tibia 10,[17][18][19] -are also associated with increased risk of developing PTOA. If future work supports this hypothesis, our finding of a twofold increase in slope for the combined ACL-LM group in comparison to the isolated ACL group may provide a biomechanical explanation for why the risk of PTOA is greater for those that suffer combined injuries to the ACL and meniscus in comparison to those that suffer isolated ACL trauma.…”
mentioning
confidence: 97%
“…As the angle decreases, there is an increased risk of graft impingement, which in turn increases tibiofemoral and patellofemoral contact load and ultimately accelerates cartilage degeneration ( Shelbourne et al, 2017 ). Mitchell found that the decrease of tibial plateau posterior inclination was related to medial femoral compartment cartilage injury ( Mitchell et al, 2018 ), which was different from previous studies, which showed increased tibial plateau posterior inclination caused cartilage injury ( Khan et al, 2014 ). However, the mechanism leading to this difference has not been clarified.…”
Section: Risk Factors Of Cartilage Lesioncontrasting
confidence: 65%
“…Increased posterior tibia slope has been suggested as not only a risk factor for initial ACL injury and the failure of ACLR graft 9,10 , but also a risk factor for OA 11 . Increased posterior tibia slope, as indicated by Tibia 7, was observed in this study especially from 6M to 1Y.…”
Section: Discussionmentioning
confidence: 99%